Peningkatan Produktivitas Penjualan UMKM Kerajinan Kulit Akasia Industry melalui Live Streaming Interaktif dan Manajemen Campaign Marketplace - Handika Asep Kurniawan; Sasmito Widi Nugroho; Dimas Nur Prakoso; Zaenal Alwan Said; Berliana Arieska Budianto (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2026)
This community service program aimed to improve the sales productivity of Akasia Industry, a leather craft small and medium enterprise (SME) located in Ringinagung Village, Magetan Regency, East Java, through the implementation of interactive live streaming and structured marketplace campaign management. The partner has operated since 2019 with 15 workers and a production capacity of 2-5 products per day, with a monthly revenue baseline of IDR 10,000,000 and approximately 100 transactions per month. The program applied a participatory action research (PAR) approach implemented across five stages: socialization and baseline mapping, technology procurement and studio setup, training, mentoring and evaluation, and program sustainability. Key outputs included a 2x2-meter mini live studio equipped with Sony ZV-E10 camera, Boya BY-V10 microphone, and LED lighting; standardized live streaming SOPs and host scripts; product photo guidelines; and structured monthly campaign calendars. Post-program outcomes showed a significant improvement in multi-platform digital presence: TikTok @akasiaindustry reached 3,655 followers with videos garnering up to 81,000 views; Instagram @akasiaindustry grew to 1,839 followers; the Shopee store achieved a 98.6% positive review rate with successful flash sale campaigns at 49% discount; and the Tokopedia store listed standardized handmade vegetable-tanned leather products. Monthly transactions increased from 100 to an estimated 160-220 orders, with market reach expanding beyond Magetan Regency.